2002
DOI: 10.1128/jcm.40.7.2346-2351.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella Serovars by PCR-Single-Strand Conformation Polymorphism Analysis

Abstract: PCR-restriction fragment length polymorphism (PCR-RFLP) and PCR-single-strand conformation polymorphism (PCR-SSCP) analyses were carried out on the 1.6-kb groEL gene from 41 strains of 10 different Salmonella serovars. Three HaeIII RFLP profiles were recognized, but no discrimination between the serovars could be achieved by this technique. However, PCR-SSCP analysis of the groEL genes of various Salmonella serovars produced 14 SSCP profiles, indicating the potential of this technique to differentiate differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 35 publications
5
27
2
2
Order By: Relevance
“…This shows that this method with the mentioned enzyme does not have the potential be applied for identification of our isolates. Nair et al using PCR-RFLP on the groEL gene amplicon of Salmonella digested with HaeIII, found a low discriminatory capacity, as only three different profiles were obtained, and different serotypes of Salmonella shared the same restriction profile (17). In our study we had eight different serotypes with four restriction profiles, which showed that our study is in agreement with their study.…”
Section: Discussionsupporting
confidence: 91%
“…This shows that this method with the mentioned enzyme does not have the potential be applied for identification of our isolates. Nair et al using PCR-RFLP on the groEL gene amplicon of Salmonella digested with HaeIII, found a low discriminatory capacity, as only three different profiles were obtained, and different serotypes of Salmonella shared the same restriction profile (17). In our study we had eight different serotypes with four restriction profiles, which showed that our study is in agreement with their study.…”
Section: Discussionsupporting
confidence: 91%
“…These include ribotyping (12), ribosomal DNA intergenic spacer amplification (22), random amplification of DNA polymorphism (35), IS200 analysis (13,38), real-time PCR (21), PCR-single-strand conformation polymorphism analysis (27), amplified fragment length polymorphism (37), sequence analysis (26), multiplex PCR (2), and DNA microarrays (8,31). Other laboratories have taken protein-based approaches to type Salmonella enterica by methods including protein arrays (7) and mass spectrometry (40).…”
mentioning
confidence: 99%
“…The widely researched targets for S. Typhi PCR-based assays include the S. Typhi flagellin gene fliC-d (Song et al, 1993;Hague et al, 1999Hague et al, , 2001Kumar et al, 2002;Prakash et al, 2005;Ambati et al, 2007;Hatta & Smits 2007;Nandagopal et al, 2010;Nath et al, 2010), the viaB region encoding the Vi antigen of S. Typhi (Hashimoto et al, 1995), the Salmonella invasion gene invA (Cocolin et al, 1998), hilA gene encoding a transcription factor of S. Typhi (Sánchez-Jiménez & Cardona-Castro, 2004), Vi polysaccharide export ATP-binding protein vexC gene (Farrell et al, 2005), ST5 gene (Aziah et al, 2007), an iron-regulated gene iroB (Bäumler et al, 1997), 5S-23S spacer region (Zhu et al, 1996), and a heat shock protein groEL gene (Nair et al, 2002).…”
Section: Gene Targets Of Pcr Based Assays For Diagnosis Of Enteric Fevermentioning
confidence: 99%
“…Cocolin et al developed a PCR-microtitre plate hybridization technique for detection of S. Typhi invA by PCR, and demonstrated enhanced sensitivity and faster availability of results in comparison to a standard agarose gel electrophoresis approach (Cocolin et al, 1998). Other PCR assays were also researched on different gene targets in order to find a rapid and sensitive detection of S. Typhi in clinical specimens (Zhu et al, 1996;Bäumler et al, 1997;Nair et al, 2002;Sánchez-Jiménez & Cardona-Castro, 2004;Farrell et al, 2005;Nizami et al, 2006;Aziah et al, 2007 ).…”
Section: Sensitivity and Specificity Of Pcr Based Assays For Diagnosimentioning
confidence: 99%